2015
DOI: 10.5194/amtd-8-11077-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The new sun-sky-lunar Cimel CE318-T multiband photometer – a comprehensive performance evaluation

Abstract: Abstract. This paper presents the new photometer CE318-T, able to perform daytime and nighttime photometric measurements using the sun and the moon as light source. Therefore, this new device permits to extract a complete cycle of diurnal aerosol and water vapor measurements valuable to enhance atmospheric monitoring. In this study we have found significantly higher triplets precision when comparing the CE318-T master and the Cimel AErosol RObotic NETwork (AERONET) master (CE318-AERONET) triplets as a result o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…This estimate is consistent with Schmid et al () who compared AOD values derived from four different solar radiometers (including an AERONET Sun‐sky radiometer) operating simultaneously together in field conditions and found that the AOD values from 380 to 1,020 nm agreed to within 0.015 (root‐mean‐square). More recently, Barreto et al () found similar results with the latest version of the Cimel. The sky radiances are calibrated versus frequently characterized integrating spheres at the National Aeronautics and Space Administration (NASA) Goddard Space Flight Center to an absolute accuracy of ~5% or better (Holben et al, ).…”
Section: Instrumentation Data and Methodologysupporting
confidence: 54%
“…This estimate is consistent with Schmid et al () who compared AOD values derived from four different solar radiometers (including an AERONET Sun‐sky radiometer) operating simultaneously together in field conditions and found that the AOD values from 380 to 1,020 nm agreed to within 0.015 (root‐mean‐square). More recently, Barreto et al () found similar results with the latest version of the Cimel. The sky radiances are calibrated versus frequently characterized integrating spheres at the National Aeronautics and Space Administration (NASA) Goddard Space Flight Center to an absolute accuracy of ~5% or better (Holben et al, ).…”
Section: Instrumentation Data and Methodologysupporting
confidence: 54%
“…The ground-measured ozone dataset was collected from the AERONET, which were retrieved from the measurements of the CE318-T Sun-Sky-Lunar spectral photometer using the Version 3 direct Sun and inversion algorithms (Barreto et al 2016;Giles et al 2018). There are three levels of AERONET operational standard product: Level 1.0 (unscreened with possible cloud contamination), Level 1.5 (cloud screened), and Level 2.0 (cloud screened and quality assured) (Zhang et al 2016).…”
Section: Datasetsmentioning
confidence: 99%
“…5(a), and of the and in Fig. 5(b), measured with triple photometer CIMEL CE318-T and obtained from Level 2.0 AERONET [35] (Version 2 algorithm) during daytime and using the algorithm described in [36] during nighttime. It can be seen that the aerosol load was roughly constant during the whole day, with only a small decrease during the first hours of the night.…”
Section: Test Casesmentioning
confidence: 99%